KETERLIBATAN ORANG TUA YANG SIBUK BEKERJA DAN PERAN ASISTEN RUMAH TANGGA DALAM PEMBENTUKAN KARAKTER ANAK - Nazara, Ester Fitri; Himmah Taulany; Swantyka Ilham Prahesti; Nufitriani Kartika Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The busy work schedules of parents often reduce the amount of time they can spend with their children, resulting in part of the caregiving responsibilities being delegated to domestic helpers. This condition makes parental involvement and the role of domestic helpers important factors in the character development of young children. This study aims to describe the involvement of working parents and the role of domestic helpers in children's character development at Cahya Mentari Daycare, Playgroup, and Kindergarten, Universitas Ngudi Waluyo, as well as to identify the forms of collaboration among parents, domestic helpers, and the school in supporting children's character development. This study employed a qualitative approach using a descriptive research method. The participants consisted of working parents, domestic helpers involved in child caregiving, and teachers at Cahya Mentari Daycare, Playgroup, and Kindergarten, Universitas Ngudi Waluyo. Data were collected through observations, in-depth interviews, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing. The trustworthiness of the data was ensured through source triangulation and technique triangulation. The findings indicate that parental involvement in children's character development is determined not only by the amount of time spent with children but also by the quality of interaction, communication, role modeling, supervision, and the cultivation of character values. Domestic helpers play a supporting role in daily childcare by encouraging children to develop discipline, independence, responsibility, honesty, and politeness in accordance with the guidance provided by parents. In addition, teachers reinforce character development through learning activities at school. Children's character development is more effective when there is good communication, shared parenting goals, and consistent collaboration among parents, domestic helpers, and the school. The implications of this study suggest that successful character development requires continuous synergy among families, domestic helpers, and educational institutions. Therefore, it is recommended that parents remain actively involved in parenting despite their work commitments, provide clear guidance to domestic helpers regarding the expected parenting practices, and maintain intensive communication with teachers to ensure that character values taught at home and at school are implemented consistently.